Il lògos e la pòlis - Dionigi, Ivano (Firenze Architettura, 2021)
The crisis of the word runs parallel to that of politics, and we should not invoke the mirage of a Babel, of ‘a single lip’, but rather the miracle of a secular Pentecost that allows us to understand each other while remaining faithful to our own language. Not the aut aut of the closed Greek pòlis, but the et et of the open Roman civitas. Suitable words for adequately designating the present, for placing, like a wise architect, the foundations on which it will be possible to build once again.